Boost multi-level NPC-fed VS large rated asynchronous pumped storage hydro-generating unit - Joseph, Anto; Kim, Seok Min; Lee, Sze Sing; Dominic, Arun; Lee, Kyo Beum (IET Electric Power Applications, 2019)
The authors intent using a boost multi-level converter for the doubly fed induction machine (DFIM) used in variable-speed pumped storage plants (VS-PSP). Voltage-source converters connected on the rotor side of the machine control the active and reactive powers of the unit. The proposed boost neutral point clamped (NPC) converter topology provides a voltage output two times larger than a conventional three-level NPC (3L-NPC) with similar DC-link voltage and equal number of switches. Hence, it increases the speed variation of the unit, which improves the efficiency during generation and pumping modes. Moreover, it reduces the starting period of the unit at the pumping mode, which is significant during mode changeover time. Furthermore, it reduces switching and conduction losses in the converter. It also reduces the total harmonic distortion in the output current, as it provides five output voltage levels. These improvements show that the boost NPC converter topology is better among VS-PSP project authorities. In addition, the reliability of the proposed topology is investigated, where converter redundancy is a challenging issue in asynchronous VS-PSP units. The proposed boost NPC was compared with the conventional 3L-NPC system by examining a 250 MW DFIM hydro-generating unit.
Keywords: Active and reactive power; Doubly fed induction machines; Generation and pumping; Multilevel converter; Neutral point clamped converters; Pumped storage plants; Total harmonic distortion (THD); Voltage source converters